Kornetov Nikolay Alekseyevich - article Editorial (Бюллетень сибирской медицины, 2004)
Here is presented a creative biography and main courses of scientific, educational and public activity of the psychiatrist, psychotherapist, researcher, pedagogue and public figure well-known in Russia and abroad, the dean of the faculty of clinical psychology and psychotherapy, the head of the chair of psychiatry, narcology and psychotherapy of the faculty of raising the level of skill and postdiploma training in Siberian State Medical University, the honored scientific worker of the Russian Federation, Doctor of Medicine, professor N.A. Kornetov.